Feeding of lion fish Pterois miles (Scorpaenidae) in the Syrian marine waters - فندي, علا; أديب زيني,; فينا حمود ,; طارق عراج, (Latakia University Journal -Biological Sciences Series, 2023)
The diet of Pterois miles, which is one of the migratory Lessepsian species that invaded the eastern coasts of the Mediterranean Sea and reached it from the Red Sea through the Suez Canal, was studied. It established abundant populations along the Syrian coast and became compete the native species on their diets, habitats and predation it. This species inhabits on cliffs, Rocky and sandy bottoms, between seagrass, artificial reefs and man-made structures at depths up to 100m. The study included analysis data of (259) individuals of lion fish, which were caught from the Syrian marine waters during a whole year (2019-2020), and the result of the study showed that this invasive species is an opportunistic general predator that poses a serious threat to the native fish wealth, as fish constitute the main food for it, followed by Decapoda, especially shrimps and crabs. Also, these invasive fish are venomous because they have spines that secrete venom, and they pose a threat to human health in general, fishermen and divers in particular may reach the point of death. Therefore, it is necessary to constantly monitor and track these invasive species, control them, and identify their biology in order to protect the native fish wealth of economic importance.